Finite-Element Simulation of Residual Stresses During the Processing of Lumped Burnable Absorber Fuel - Mistarihi, Qusai; Ryu, Ho Jin (Frontiers in Energy Research, 2021)
UO2–Gd2O3 fuel is mostly used as a burnable absorber fuel in the form of a homogenous mixture of Gd2O3 and UO2. More effective reactivity control can be achieved by lumping Gd2O3 within the UO2 because this enhances the spatial self-shielding factor of the burnable absorber fuel. The fabrication of lumped burnable absorber fuel containing lumped Gd2O3 spherical particles or compacts has been experimentally demonstrated using yttrium-stabilized zirconia (YSZ) as a UO2 fuel surrogate. Interfacial cracks or gaps forming under the interfacial stress that develops during the fabrication of the fuel can be eliminated by controlling the initial density of the lumped Gd2O3. In this study, this interfacial stress during the fabrication process was simulated using finite element methods. The effect of the size, shape, and initial density of the lumped Gd2O3 on the distribution and magnitude of the interfacial stress was investigated. The addition of Gd2O3 spherical particles resulted in a lower and more uniform interfacial stress distribution than the addition of cylindrical Gd2O3 compacts. The interfacial stress was increased with increasing Gd2O3 size and initial density. The calculated interfacial stress was compared with experimental results to estimate the threshold stress for crack development in a lumped burnable absorber fuel.